‘Do you understand how much I have transgressed here?’: interrogating dynamics and consequences of noticing in the post-colonial legal self - Aiste Janusiene (Law Text Culture, 2021)
This paper explores conditions of noticing through reflective analysis of emerging awareness in the postcolonial legal self. By unpacking Lithuanian judges’ involvement with popular culture, I explore how theatrical jurisprudence as performed through judges contributes to the transformation of understanding about the judicial role both for judges and the researcher. Since 1990 when Lithuania started a transition from a totalitarian system to democracy, the role of a judge is undergoing substantial change. In the reflexive analysis of data collected from interviews and focus group discussions with Lithuanian judges, I interweave post-colonial theories insights with theatrical jurisprudence to take implications of post-colonial legal identity seriously. In this paper, I clarify how awareness of a body (trans)forms an understanding of the judicial role and the consequences of body negation. I explore the inability to notice the law’s effects and consequences of judges whom I identified as body ignorant. Also, while emerging awareness of a body for judges acts transformative, I argue that embrace of a body is insufficient to foster the ability to notice injustice in the conditions created on the tension between the fiction and reality. I am indebted to theatrical jurisprudence (Leiboff, 2019) for being able to register a sacrifice of a courageous Lithuanian judge who through his transgressions created conditions for noticing injustice of instrumental law and algorithmic judging. In the context of transition from dogma to practice, responses to Judge Brook’s theatrical challenges animate not just post-Soviet legality but also a wider shift towards the digital legalities.